Resolving the Illicit Trade of Small Arms and Light Weapon through ASEAN Ministerial Meeting on Transnational Crime (AMMTC) - Putti Ananda Hiswi (Department of Government Studies Universitas Muhammadiyah Makassar, 2018)
This paper analyses the cooperation of states in Southeast Asia within the framework established by ASEAN, that is ASEAN Ministerial Meeting on Transnational Crime (AMMTC) to resolving the illicit trade of Small Arms and Light Weapon in the region. Most of existing works on the topic being studied put emphasize on the importance of the existence of norms, the role of institutions and security cooperation in resolving the illicit weapons trade. However, the existing studies have not explained why the existing form of cooperation has not been effective. By the approaching of international regime theory, this article explains the interest based of regime that explain the background of regime formation which could influence state behavior to cooperate and successfully implement the rules of the international regime itself. The research applying qualitative research methods with data sourced from primary and secondary data from ASEAN official documents, books, journals, online news. This article shows that the effectivity of AMMTC to deal with the illicit Small Arms Trade is strongly influenced by the implementation commitment of the state members.